Development of the retinotectal projection in zebrafish embryos under TTX-induced neural-impulse blockade - Stuermer, CA (J Neurosci, 1990)
The influence of neural activity on the morphology of retinal-axon- terminal arbors and the precision of the developing retinotectal projection in zebrafish embryos was explored. Terminal-arbor morphology and their distribution in the tectum was determined with anatomical fiber-tracing methods using the fluorescent dyes dil and diO. To allow development under activity-deprived conditions, TTX was injected into the eyes of 30-38-hr-old zebrafish embryos at concentrations that effectively blocked neural activity both in retinal ganglion cells and throughout the CNS. Much like axons with normal neural-activity patterns, activity-deprived axons from dorsal and ventral and from temporal and nasal regions in the retina terminated over retinotopically appropriate and nonoverlapping regions of the tectum. Even after ablation of 1 hemiretina at the time of axonal outgrowth, activity-deprived axons from the remaining hemiretina grew directed toward and arborized selectively within their retinotopically appropriate tectal half in the same way as would nondeprived axons. Besides being retinotopic, the area over which small populations of activity-deprived axons from neighboring ganglion cells arborize is as small as that of active axons. The size of terminal arbors of retinal ganglion cell axons was unaffected by blockade of neural activity. The mean terminal-arbor size was 27 x 18 microns for the TTX-injected and 31 x 22 microns for the control embryos. The tectal coverage of TTX- blocked and control axons was equally small, with values of 1.4% and 1.6%, respectively. These data show that a precisely organized retinotopic map in developing zebrafish forms independent of neural- impulse activity.